2017
DOI: 10.21315/mjms2017.24.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Intervention towards Obesity and Blood Pressure among Housewives in Klang Valley: A Quasi-Experimental Study

Abstract: Background: The obesity rate in Malaysia is the highest in Asia. Half its population is obese or overweight. The present study aims to determine the effects of lifestyle intervention on weight loss and blood pressure among Malaysian overweight and obese housewives in Klang Valley.Methods: A quasi-experimental study with 328 obese and overweight low socioeconomic status housewives aged 18-59 years old who met the screening criteria participated in the study. They were recruited into an intervention group (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Thirteen studies used education and counseling intervention strategies [ 24 , 25 , 27 37 ]; four studies used management intervention strategies [ 18 , 19 , 38 , 39 ]; seven studies combined education, counseling and management intervention strategies [ 26 , 40 45 ]; and six studies used screening and referral for management intervention strategies [ 16 , 17 , 46 49 ]. Fourteen studies followed participants for less than 12 months (i.e., short-term interventions) [ 17 , 26 , 27 , 29 , 30 , 32 34 , 36 , 40 43 , 45 ]. Twelve studies were conducted in the US [ 16 , 17 , 19 , 24 , 27 , 28 , 32 , 33 , 39 , 41 , 43 , 46 ] and most studies included both genders [ 16 19 , 24 26 , 28 31 , 33 49 ] and all racial/ethnic groups [ 16 19 , 24 40 , 42 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies used education and counseling intervention strategies [ 24 , 25 , 27 37 ]; four studies used management intervention strategies [ 18 , 19 , 38 , 39 ]; seven studies combined education, counseling and management intervention strategies [ 26 , 40 45 ]; and six studies used screening and referral for management intervention strategies [ 16 , 17 , 46 49 ]. Fourteen studies followed participants for less than 12 months (i.e., short-term interventions) [ 17 , 26 , 27 , 29 , 30 , 32 34 , 36 , 40 43 , 45 ]. Twelve studies were conducted in the US [ 16 , 17 , 19 , 24 , 27 , 28 , 32 , 33 , 39 , 41 , 43 , 46 ] and most studies included both genders [ 16 19 , 24 26 , 28 31 , 33 49 ] and all racial/ethnic groups [ 16 19 , 24 40 , 42 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings in this review, highlight that, quasi-experiments are increasingly used to evaluate the effectiveness of health interventions for hypertension management when RCTs are not feasible or appropriate. For instance, several studies included in our systematic review often indicated that RCTs would have been difficult to be implemented given that the intervention was conducted in a particular setting such as a pragmatic clinical setting [ 16 , 43 , 45 , 48 ], a community setting [ 24 , 35 , 36 , 42 ], or a real-world organizational setting [ 33 ] because of ethical concerns and human resources issues. Another reason why quasi-experiments were chosen had to do with the need for translation and generalizability of the evidence in a specific community setting [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation methods included both objective and subjective methods (45.8%), subjective methods only (44.6%) and objective methods only (8.4%). Reported outcomes included weight, BMI and other anthropometric measures [ 23 , 53 , 71 , 73 75 , 77 , 79 , 80 , 82 , 84 , 85 , 87 , 89 , 91 95 , 98 , 100 , 101 , 103 112 , 114 , 115 , 117 120 , 124 ], reemployment [ 22 , 47 , 52 , 54 , 57 , 59 , 61 , 62 , 65 , 67 69 ], healthy eating knowledge and healthy eating behaviour [ 49 , 56 , 72 , 74 , 76 , 78 , 87 , 98 , 100 , 110 , 111 , 113 , 118 120 , 124 ], self-efficacy and self-esteem [ 27 , 48 51 , 54 , 56 , 57 , 59 , 61 , 66 70 , 72 , 75 , 76 , 78 , …”
Section: Resultsmentioning
confidence: 99%
“…El principal hallazgo de este estudio demostró una mayor asociación en las dueñas de casa mayores a 55 años de cumplir las recomendaciones de estilos de vida saludable en comparación al grupo más joven (< 40 años). Principalmente, aquellas relacionadas con el consumo de alcohol y tabaco; ta la AF, es pertinente fomentar hábitos de AF en este grupo de la población a través de programas específicos que podrían repercutir positivamente sobre su peso corporal y presión arterial, tal como ha sido demostrado previamente 26,27 . En el aspecto relacionado al estilo y calidad de vida en esta población, se ha observado una moderada-alta valoración por parte de las dueñas de casa 28 .…”
Section: Discussionunclassified